2020
DOI: 10.1002/brb3.1524
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social cognition network in young adults with autism spectrum disorder using graph analysis

Abstract: Background Autism spectrum disorder (ASD) is characterized by an impairment in social cognition (SC). SC is a cognitive construct that refers to the capacity to process information about social situations. It is a complex network that includes distinct components. Exploring how SC components work together leads to a better understanding of how their interactions promote adequate social functioning. Our main goal was to use a novel statistical method, graph theory, to analyze SC relationships in ASD and Typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…In recent times one of the computational concepts like the graph properties plays a significant role in analysing a network by exploring the accessibility of nodes [21] . Of which Multi-graph [3] , [17] can represent the complex relational data of a network and works well provided that the significant changes are made only to the existing graph analysis algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times one of the computational concepts like the graph properties plays a significant role in analysing a network by exploring the accessibility of nodes [21] . Of which Multi-graph [3] , [17] can represent the complex relational data of a network and works well provided that the significant changes are made only to the existing graph analysis algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is a heterogeneous group of neurodevelopmental disorders, which present a substantial challenge to explore interrelations across several distinct components of the various severity of symptoms [ 1 , 2 ]. The core symptoms of ASD included deficits in social communication and social interactions, which are reflected by impairment of social cognition abilities.…”
Section: Introductionmentioning
confidence: 99%
“…According to Happe and Frith [ 3 ], social cognition can be represented as an elaborate network graph that contains several components, such as emotion processing, empathy, and theory of mind (ToM). Futhermore, Vagnetti et al [ 2 ] found that, compared to typically developing (TD) individuals, the ASD group showed less connection in their constructed network topology of social cognition and had inefficient connections among the components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with a study by Webb and collaborators [ 18 ]: they found that early signs of risk of subsequent ASD diagnosis include decreased use of facial information, including failure to look at the faces of social partners and failure to use eye gaze for joint attention. Individuals with ASD are characterized by altered and impaired processing of social information [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%